Concepts in cereal chemistry - MacRitchie, Finlay (Boca Raton, FL : CRC Press, 2010)
'Compact and reader friendly, this book explores methods for improving quality in breeding and the health benefits of food. Written by a distinguished researcher and teacher, the book emphasizes the multidisciplinary nature of the field. While focusing mainly on the chemistry, the author brings in relevant theory from basic science such as physics and genetics. Exercises are included at the end of most chapters. Suggested solutions are given at the end of the book. The solutions to the exercises require thinking and, in some cases, searches of the literature. Demonstrations are included to illustrate principles.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Cereals as food -- Analysis; Grain -- Biotechnology